Word order variation of the verbal sentence in a Jerusalam-amarna letter, EA 290 - Westhuizen, Johannes P. van der (Journal for semitics, 2016)
The reason for the correspondence between the vassals of Syria-Palestine and their sovereign, the pharaoh of Egypt, is instigated by the external and internal turmoil in Syria-Palestine during the Late Bronze Age. These letters were written in the Western Peripheral Akkadian dialect (WPA) with some West Semitic (WS) trends, by the scribes of the vassals in Israel and the scribes of the pharaoh. One such trend is the word order, and variations from it, in the verbal sentences. This variation in word order was to effect some special emphasis or some nuance of the appropriate element in the specific sentence. The variation in word-order was brought about by certain (emphasising) words such as anuma, sanita, inuma and amurmi and/or constructions such as subject fronting or object fronting, parallel sentence arrangement and chiastic sentence arrangement. However, even this word order and the variation thereof shows no consistency. The investigation of the word order and its variation functioning in the verbal sentences of the Jerusalem-Amarna letters as in EA 285-290 to the pharaoh shows that these Amarna letters -even those with similar content as in the other letters to the pharaoh must have been written by the different scribes of the vassals. This leads to the conclusion that each scribe had his own version of an "interlanguage" that he used in his correspondence.